Annemer and Coolie: Social Reflection in Peranakan Chinese Literary Works - Dharma, Laga Adhi; Septiani, Nur Alifah (Humanis, 2023)
The products of literary works often present events closely related to the social context. One of the Chinese Peranakan literary works that reflects social phenomena is Sya’ir Jalanan Kreta Api. This study aims to describe the forms of social reflection and how literature relates to its history. The theory used in this study is the theory of sociology of literature put forward by Alan Swingewood. The method of data analysis is carried out by sorting and grouping qualitative data so that certain relations can be determined between one data category and another. The results obtained are that there is a social reflection on the phenomenon of land compensation and modernization in the Java region, as well as several historical events represented in the Sya’ir Jalanan Kreta Api about Chinese people as Annemer, the empowerment of local communities as coolies and the performance of dependent Annemer on coolies.